The Impact of Intermittent Hypoxemia on Left Atrial Remodeling in Patients with Obstructive Sleep Apnea Syndrome - Yung-Lung Chen; Yung-Che Chen; Hui-Ting Wang; Ya-Ting Chang; Yen-Nan Fang; Shukai Hsueh; Wen-Hao Liu; Pei-Ting Lin; Po-Yuan Hsu; Mao-Chang Su; Kuo-Tung Huang; Meng-Chih Lin (Life, 2022)
Obstructive sleep apnea syndrome (OSAS) is a significant risk factor for left atrial (LA) remodeling. Intermittent hypoxemia occurs during the sleep cycle in patients with OSAS and plays a crucial role in cardiovascular pathologies such as stroke, arrhythmia, and coronary artery disease. However, there is very little information about the role of intermittent hypoxemia in LA remodeling in patients with OSAS. In total, 154 patients with sleep-related breathing disorders (SRBD) were prospectively recruited for this study. All enrolled SRBD patients underwent polysomnography and echocardiography. Significant OSAS was defined as an oxygen desaturation index (ODI) of ≥10 per hour. Intermittent hypoxia/reoxygenation (IHR) stimulation was used to test the effect of hypoxia on the viability, reactive oxygen species, apoptosis, and inflammation-associated cytokine expression in the HL-1 cell line. To investigate the effect of patients’ exosomes on HIF-1 and inflammation-associated cytokine expression, as well as the relationship between ODI and their expression, exosomes were purified from the plasma of 95 patients with SRBD and incubated in HL-1 cells. The LA size was larger in patients with significant OSAS than in those without. There was a significant association between ODI, lowest SpO2, mean SpO2, and LA size (all p < 0.05) but not between the apnea–hypopnea index and LA size. IHR condition caused increased LDH activity, reactive oxygen species (ROS) levels, and apoptosis in HL-1 cells and decreased cellular viability (all p < 0.05). The expression of HIF-1α, TNF-α, IL-6, and TGF-β increased in the IHR condition compared with the control (all p < 0.05). The expression of HIF-1α, IL-1β, and IL-6 increased in the HL-1 cells incubated with exosomes from those patients with significant OSAS than those without (all p < 0.05). There was a significantly positive correlation between ODI and the expression of HIF-1α, TNF-α, IL-1β, IL-6, and TGF-β; a significantly negative correlation between mean SpO2 and IL-6 and TGF-β; and a significantly negative correlation between the lowest SpO2 and HIF-1α (all p < 0.05). In conclusion, intermittent hypoxemia was strongly associated with LA remodeling, which might be through increased ROS levels, LDH activity, apoptosis, and the expression of HIF-1α and inflammation-associated cytokines.